O Carste Jandaíra, Bacia Potiguar, e suas implicações para a qualidade de reservatórios - Bagni, Fábio Luiz (2021)
Predicting sub-seismic structures in carbonate reservoirs is a technological gap for reservoir models and new exploration targets. This study aims to understand the geological controls on the permeability-porosity distribution in fractured and karstified carbonates rocks of the Jandaíra Formation, Potiguar Basin, Brazil. The present study investigates the concentration of karst in an anticlinal hinge zone and below a subaerial unconformity. This study area lies in a karstic valley formed by collapse of galleries and cave walls. The methodology integrates satellite and UAV imagery, digital terrain model, 2D seismic data, exploratory well logs, field, and laboratory (mineralogy, geochemistry, petrology, petrophysics) data. A regional-scale fold with a NE-SW-oriented axis plunging to NE occurs in the area. It is parallel to the current drainage of the Apodi-Mossoró River and consistent with an NW-SE-oriented compression in a strike-slip stress field. Our findings indicate that fracture intensity is higher in fold limbs, forming a high-permeability roughly vertical high-permeability corridor. Far from the fold limb, the karst features are mainly at the surface. In addition, caves systems and conduits are concentrated below subaerial unconformities, which was formed by superposed epigenetic dissolution. The sedimentary sequence below the unconformity is composed of dolomitic peritidal deposits, whereas the sequence above the unconformity consists of tight-cemented calcite subtidal deposits. The karst features associated with the unconformity form a highpermeability zone of regional extent. Both sequences are recognized across the basin. The present study show that superposed rock exposure, fracturing, and hydrological dynamics are key elements that influence epigenic karstification of carbonate reservoirs. They control the lateral reservoir zonation, whereas faults and fractures concentrate porosity within the vadose/phreatic hydrological zones. This study presents a multidisciplinary and multiscale approach to analyze the karstification in carbonate rocks. It contributes to predicting the occurrence, distribution, and concentration of karst features in carbonate units and the consequent increase in permeability-porosity in carbonate reservoirs.